Teaching Resources Research Development Grant 2022 by the Ministry of Education, People's Republic of China - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
Teaching Resources Research Development Grant 2022 by the Ministry of Education, People's Republic of China was awarded to Associate Professor Dr Goh Chin Shuang, Associate Professor Dr Airil Haimi Mohd Adnan, and Madam Zhang Huiqin@ Ayisha for their research, 'Integrating AR and AI Technologies in the Development of Malaysian Localized Teaching Resources.' The three researchers along with seven others from Kunming University of Science and Technology, China obtained RM75,305 to complete the project that aims to develop a prototype of an application for Mandarin language teaching and learning. The project that has been initiated on 10th December 2022, is expected to be accomplished in a year. Congratulations to every team member on securing the grant!